PROFIL PEMENUHANKEBUTUHAN PSIKOLOGIS PESERTA DIDIKKELAS TINGGI OLEH GURU (Studi pada Kelas V dan VI di SD Kemala Bhayangkari Padang) - Anggraini, Eka Sri (Bimbingan dan Konseling, 2014)
The problem of this research was found that, there is still unfufuill a studentâspsychological needs. This is proven by extant teacher who do discriminating their students such asthe teacher more love the smarter and prettier students, Judging students that make then becomelazy and penetrated their school. So the teacher expressed the anger that shouldnât have been likecold them,hit them with things and judge them with bad words. The aim of this research are todescribe : 1) The fulfillment profil studentâs need visible from aspects of curiosity cherished by theteacher in the school. 2) The fulfillment profil studentâs needs visible from aspect wants to beappreciated by the teacher in the school. 3) The fulfillment profil studentâs needs visible fromaspect of self-actualization by teacher in the school. This research is quantitative describtiveresearch. Population in this research are all students in class V and VI in SD Kemala BhayangkariPadang as much as 112 students. Sampl in this research use purposive sampling technique that ishow asample with certain considerations or for certain purpose,so sampling in this research asmuch as 33 students. Data collectedwith a questionnaire,whereas data analysis technique usepresentation analysis of the percentage. The result of this research recomendated to teacher inorder to increase fulfill way the studentâs psychological needs both in term of compliance want tolove sense needs,compliance want to be valued needs,and compliance self-actualization ormanifest itself so all studentâs psychological needs met with good.